O que os olhos veem quando eles me leem : um olhar sobre o adolescente em conflito com a lei - Albuquerque, Deisiane Rodrigues de (2021)
This research begins with a concern regarding the mandatory use of the Individual Care Plan (PIA) as a methodological instrument to monitor adolescents in compliance with the Socio-Educational Measure (MSE), after the creation of Law 12594/12. The document is proposed to guide the actions to be taken in order to ensure the full protection of these young people. In that document, the subject's position is produced through the construction of a profile for these young people admitted to MSE units. Thus, the main objective of this dissertation was to conduct a study on the production of the profile of adolescents in conflict with the law that complies/complied with socio-educational measure of deprivation of liberty internment from the PIAs elaborated in the State of Sergipe. For this, we start from ideas inspired by Erving Goffman and Michel Foucault about the issue of stigma, discipline and biopower. The research has a descriptive and analytical character, articulating documental study procedures, informal reports, comparative study, crossing of quantitative data and bibliographical research in the history of child care in Brazil. A total of 453 PIAs produced in Sergipe from 2014 to 2019 were analyzed. The results indicate that the PIA is adjusting to the criteria it consolidated. In practice, it still challenges the system. Thus, although SINASE recommends the PIA as a document used to enforce rights, built with the adolescent and their family, it ends up serving as a document that creates a profile for the adolescent from a context of evidence that will be forwarded to the judge evaluates the normative actions of the State.